Determination of Acai River Quality Status, Jayapura City Through Pollution Index Method Based on Its Designations - Annisa Novita Sari; Diki Kurniawan (Journal of Aquaculture Development and Environment, 2019)
The river is a natural and/or artificial water channel or container in the form of a water drainage network with water in it, from the upstream to the estuary, with the right and left borders bounded by the boundary line. The problem that often occurs in the river area is pollution. This research is focused along the Acai River flow located in Abepura District, Jayapura City, Papua Province. Problems that often occur along the Acai River flow in Jayapura City are the accumulation of garbage in the river body and changes in the physical condition of the river, both color and odor. Therefore, the purpose of this study is to determine the status of water quality from the Acai River so that it can be used as a reference in determining the sustainable management of the Acai River. The method used to determine the status of water quality was the pollution index method. Measurements were carried out in the upstream, middle and downstream parts of the Acai River. The results showed that the Acai River Pollution Index (PI) in the upstream reaches ranged from 1.75 to 5.35. The middle part of the Acai River has a Pollution Index (PI) of 1.84 - 5.41, and the downstream part has a PI of 1.78 - 5.39. Based on these data it was known that the overall Pollution Index (PI) in the Acai River ranges between 1.75 - 5.41. Pollution that occurs in the Acai River was caused by pollution of organic material obtained from domestic waste. This was shown from the results of measurements of water quality where BOD levels are 2.58 - 4.54 mg / L and COD is 190 - 193 mg / L. The Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) levels of the Acai River have exceeded water quality standards. Based on the measurement results of the Pollution Index (PI) it can be concluded that the Acai River has experienced pollution from the low to moderate categories, for water classes ranging from Class I to Class IV. For this reason, it was suggested that an integrated domestic waste treatment plant be made which can accommodate domestic waste as a result of community activities and process it first before finally being discharged into the river water body.